Analisis Keragaman Gulma pada Tanaman Jagung di Kelompok Tani Usaha Maju, Desa Naibonat, Kecamatan Kupang Timur, Kabupaten Kupang - Benu, Opa Nikolas; Nenotek, Petronella S.; Nahas, Agustina E.; Simamora, Agnes V.; Serangmo, Diana S.; Kapa, Max J.; Mudita, I Wayan; Kana, Yeni Radja (Wana Lestari, 2022)
The purpose of this study was to analyze the diversity of weed species in corn plantings in the Usaha Maju Farmer Group, Naibonat Village, East Kupang District, Kupang Regency which took place from July to December 2020. Observation of weeds was carried out using the quadratic method. Observations in the sample plots by making observation subunits measuring 1 x 1 m2. Unknown weed species were collected and then identified using the Plant Snap application and making a herbarium. The results showed that there were 13 weed species found associated with corn plants, namely Eleusine indica, Setaria pumila, Echinochloa colona, Cynodon dactylon, Digitaria ciliaris, Xanthium strumarium, Centela asiatica Ipomoea obscura, Euphorbia hirta, Tridax procumbens, Spigelia anthelmia, Passiflora foetida, and Phyllanthus niruri. Based on vegetation analysis, Eleusine indica and Euphorbia hirta were more dominant than other weed species with absolute densities of 20.5m2 and 21.3m2 per maize plant, respectively.